INFLUENCE OF THE AGRICULTURAL SECTOR AND INDUSTRIAL SECTOR ON LABOR ABSORPTION IN LUWU NORTH - Isa, Isa; Halisa, Marshanda Nurul; Sari, Idha; Aris, Arini Lestari (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
ABSTRACTPopulation growth must continue to be balanced with job growth to absorb labor in order to reduce the problem of unemployment. Unemployment is a situation where a person who is registered in the labor force wants to get a job but has not gotten one. The aim of this research is to determine the influence of the agricultural sector and the industrial sector on labor absorption in North Luwu. The data collection techniques used in this research are library research and the Central Statistics Agency (BPS). The results of this research show that the agricultural sector and the industrial sector simultaneously have an influence significant impact on labor absorption in North Luwu Regency. The agricultural sector does not have a significant effect on labor absorption in North Luwu Regency and the industrial sector does not have a significant effect on labor absorption in North Luwu Sector Regency.Keywords: Agricultural Sector; Industrial Sector; Sector and WorkforceABSTRAKPertumbuhan penduduk harus terus diimbangi dengan pertumbuhan lapangan pekerjaan untuk menyerap tenaga kerja agar dapat mengurangi masalah pengangguran. Pengangguran adalah keadaan dimana seseorang yang terdaftar dalam angkatan kerja ingin mendapatkan pekerjaan tetapi belum mendapatkannya. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh sektor pertanian dan sektor industri terhadap penyerapan tenaga kerja di Luwu Utara. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah penelitian kepustakaan dan Badan Pusat Statistik (BPS). Hasil penelitian ini menunjukkan bahwa sektor pertanian dan sektor industri secara simultan berpengaruh signifikan terhadap penyerapan tenaga kerja di Kabupaten Luwu Utara. Sektor pertanian tidak berpengaruh signifikan terhadap penyerapan tenaga kerja di Kabupaten Luwu Utara dan sektor industri tidak berpengaruh signifikan terhadap penyerapan tenaga kerja di Kabupaten Luwu Utara.Kata kunci: Sektor Pertanian; Sektor Industri; Sektor dan Tenaga Kerja